DAMPAK PRAKTIKUM SIARAN RADIO TERHADAP KEMAMPUAN BERBICARA DI DEPAN UMUM STUDI KASUS MAHASISWA KOMUNIKASI - Winda Kustiawan; Abdul Rahman Pais Nasution; Farhan Sauqi Abdi Harahap; Muhammad Hafiz Sapriadi; Muhammad Izwan; Rakhas djuniardi (Jurnal Publikasi Manajemen Informatika, 2025)
This study aims to analyze the impact of radio broadcasting practicums on the public speaking abilities of Communication and Islamic Broadcasting students at the State Islamic University of North Sumatra. A qualitative approach was employed, involving observations and semi-structured interviews with five active participants in the broadcasting practicum. The findings reveal that radio broadcasting practicums significantly enhance students' speaking skills, through improved articulation, intonation, and effective listening abilities. Factors such as direct interaction with listeners and strong academic support were found to be crucial in facilitating these improvements. The study recommends enhancements to practicum facilities, integration of more effective feedback sessions, and emotional management training to support students in handling the pressures of live broadcasting.